ANALISIS PERUBAHAN CUACA TERHADAP KENAIKAN HARGA BERAS - Fatmawati, Kenia; Dwi Nur Rahmawati; Putri Dalya; Saodin (MUHKAL, 2024)
The spike in rice prices along with extreme weather changes has attracted the attention of the PKM team to conduct further PKM. This PKM aims to find out the correlation between weather and rice price increases. To gain an in-depth understanding, the PKM team conducted interviews with farmers in Agom village. The results show that weather has a major influence on the rising price of rice. This result underscores the importance of highlighting the significant impact of weather in regulating rice prices. The implication of these results is that the government can develop strategies to reduce the risk of weather-induced rice price fluctuations. One strategy that can be implemented is to increase fertilizer subsidies. With this subsidy, farmers can obtain fertilizers at affordable prices, thus increasing rice productivity even in the face of extreme weather changes. In addition, the government can also provide borehole assistance to help overcome water shortages during the dry season. Thus, both measures will help improve food security and farmers' welfare in the future.